Analysis of Preventive Maintenance and Breakdown Maintenance on Production Achievement in the Food Seasoning Industry - Indra Setiawan; Ahmad Bahrudin; Moh. Mawan Arifin; Wahyu Inggar Fipiana; Vivi Lusia (OPSI, 2021)
The machine is a facility that is necessary for the company in production. The machine can reduce the failure rate of the product and reach the target time according to the customer's request. Therefore the machine needs to be cared for and maintained. Maintenance and care is a way to prevent the machine from being damaged. This study aims to determine and analyze the effect of preventive maintenance and breakdown maintenance on production achievement. The research was conducted in the Food Seasoning Industry. The research population is maintenance employees and production employees. The sample used was 25 respondents based on employees who are experts in their fields. The analytical method used in this research is the descriptive analysis method with a quantitative approach with linear regression analysis. Data processing using the help of IBM Statistics 21.00 software. The results showed that preventive maintenance partially had a significant effect on production achievement. Breakdown maintenance partially has no significant effect on the achievement of production. Simultaneously preventive maintenance and breakdown maintenance have a significant effect on the achievement of production. Linear regression analysis resulted in the model formula Y= 9.004 + 0.561 (X1) + 0.042 (X2)